The Electronic Logging Device Mandate, Hours of Service Rules, and Implications for Southwest Florida Produce Haulers - Fritz Roka; Tara Wade; Craig Sprouse (EDIS, 2019)
Electronic logging devices, or ELDs, became mandatory for commercial motor carriers December 18, 2017. The compliance timeline for the produce industry was delayed with two 90-day waivers. On June 18, 2018, however, ELDs became mandatory for produce haulers as well. The primary purpose behind requiring ELDs was to ensure greater compliance with existing hours of service requirements by motor carriers and their drivers. This 5-page fact sheet written by Fritz Roka, Tara Wade, and Craig Sprouse and published by the UF/IFAS Food and Resource Economics Department reviews HOS rules, clarifies agricultural exceptions to the HOS rules, and offers a preliminary discussion as to how ELDs could affect south Florida produce growers. edis.ifas.ufl.edu/fe1052